Avoidance of instable photoluminescence intensity from AlGaN bulk layers. Issue 8 (9th June 2017) - Netzel, Carsten; Jeschke, Jörg; Knauer, Arne; Weyers, Markus
Abstract : The emission intensity from c‐plane AlGaN bulk layers changes strongly on time scales from seconds to hours during above band gap illumination in photoluminescence experiments. Responsible for this effect is the accumulation of photo‐generated charge carriers at the semiconductor surface, modifying surface states and surface recombination. The effect has a negative impact on the exactness and comparability of photoluminescence intensity measurements, especially for measurements with long exposure times or repeated excitation on the same spot. We realized temporally stable photoluminescence intensity by using an AlN cap layer separating the studied AlGaN bulk layer from the crystal surface. We verified the temporal stability in temperature‐dependent photoluminescence measurements in vacuum and in ambient air. Surface recombination was suppressed for the capped AlGaN layer, resulting in significantly higher emission intensity at room temperature.